2012
DOI: 10.1002/rra.2557
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Compensation Releases: Impact on the Macroinvertebrate Community of the Derwent River, Northumberland, Uk—a Longitudinal Study

Abstract: River regulation for the purposes of public water supply causes the flow regime downstream of a dam to change. Traditionally, in the UK, such regulation was accompanied by requirements for reservoir releases to compensate downstream water users (e.g. industry) for the loss of natural flow (compensation flows). In this article, we compare a unique pre-impoundment macroinvertebrate data set for a regulated upland river with survey data post-impoundment. This allows a longitudinal assessment of the response of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…Increasing minimum flows has been shown to increase the ecological integrity of benthic aquatic insect and fish communities (Connor and Pflug 2004;Bednarek and Hart 2005;Decker et al 2008;Bradford et al 2011), but these studies often restore flows with the purpose of rewetting previously dry reaches instead of increasing existing flows (but see Travnichek et al 1995). However, in a long-term study Maynard and Lane (2012) found that increased minimum flows led to an increase in macroinvertebrate diversity. Nevertheless, studies investigating the relationship between minimum flows and freshwater mussel diversity are rare in spite of their more imperiled conservation status.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…Increasing minimum flows has been shown to increase the ecological integrity of benthic aquatic insect and fish communities (Connor and Pflug 2004;Bednarek and Hart 2005;Decker et al 2008;Bradford et al 2011), but these studies often restore flows with the purpose of rewetting previously dry reaches instead of increasing existing flows (but see Travnichek et al 1995). However, in a long-term study Maynard and Lane (2012) found that increased minimum flows led to an increase in macroinvertebrate diversity. Nevertheless, studies investigating the relationship between minimum flows and freshwater mussel diversity are rare in spite of their more imperiled conservation status.…”
Section: Conservation Implicationsmentioning
confidence: 99%
“…Additionally, responses of some taxonomic groups have been observed to vary, for example, no change or decrease in abundance of Coleoptera (Spence and Hynes, ; Nichols et al ., , respectively). Furthermore, varied responses in diversity have also been observed (increased: Penaz et al ., ; decreased: Pearson et al ., ; Poole and Stewart, ; Armitage, ; Munn and Brusven, ; Maynard and Lane, ). Further research is required to both clarify and understand the mechanisms behind these differential responses.…”
Section: Introductionmentioning
confidence: 99%
“…regulated or unregulated) rather than more detailed ‘continuous’ descriptors of the extent of regulation (ER) across the catchment. The scale at which research has been undertaken may also be important: Research conducted on single rivers (Petts et al ., ; Maynard and Lane, ) has identified clear impacts but has the shortcoming of failing to identify patterns over larger scales. Regional‐scale studies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Regulation appears to severely constrain the absolute differences between daily flows, also indicated by the lack of low and high‐flow occurrences overall, especially at the Moar flow directly downstream of Stronuich (Figures and ). Maynard and Lane () also found decreases in the frequency of high and low flows related to river impoundments with minimum compensation flows, in a catchment with an unusually long‐term data record that spans pre‐river and post‐river impoundments. In terms of volumes, the total discharge is reduced because of the net export of water transfers (Figure ), as also suggested by Birkel et al .…”
Section: Discussionmentioning
confidence: 97%
“…As such, the results of the impact assessment here suggest that a first step towards more ecologically based release regimes in the river Lyon would be to provide more variability in flows downstream of Stronuich. However, despite the evident regulation impacts on flows in the Lyon, previous studies have suggested that the impacts on invertebrates might be quite localized (Jackson et al ., ; Maynard and Lane, ).…”
Section: Discussionmentioning
confidence: 99%